ELR-led economic development: a plan for Tunisia - Fadhel Kaboub (Levy Economics Institute of Bard College, 2007)
This paper establishes the financial feasibility of an employer-of-last-resort (ELR) program in a small developing country like Tunisia. It argues that an ELR-led economic development policy is vastly superior to the traditional import substitution industrialization (ISI), export-led, and FDI-led development models, all of which Tunisia has adopted without much success in reducing unemployment. Despite outperforming its peers in terms of macroeconomic stability, Tunisia's official unemployment rate still hovers around 15 percent, with two-thirds of first-time job seekers having university degrees. The paper demonstrates that a well-targeted ELR program can be gradually introduced over a six-year period to remedy this problem by reclaiming sovereignty over the country's domestic monetary and fiscal policies under a floating exchange rate regime. The estimated ELR net wage bill would be around 2.7 percent of GDP; however, spending by ELR workers would offset program costs, and the net effect on GDP would be an increase of about 3.6 percent. The paper concludes by proposing a set of complementary policy reforms that must accompany an ELR program to ensure long-term growth sustainability along with full employment and price stability.
Keywords: B5; O11; O23; O55; E24; E62; H63; 330; Tunisia; ELR; Full Employment; Unemployment; Job Creation; Functional Finance; Flexible Exchange Rate; Development; Export-led Growth; FDI-led Growth; ISI